Effect of prickly pear and algarrobo pod syrup coatings on consumer acceptance and stability of roasted almonds - Gayol, Maria Fernanda (2009)
The objective of this study was to evaluate the oxidative stability of roasted almonds coated with prickly pear and algarrobo pod syrups and the effect of these coatings on the consumer acceptance. RESULTS: Prickly pear syrup had higher moisture, proteins, ashes and lipids, and less carbohydrate content than algarrobo pod syrup. Phenolics and antioxidant activity such as inhibition percentages of diphenyl picryl hydrazyl radical were higher in prickly pear syrup than algarrobo pod syrup. Roasted almonds had higher protein and lipid contents and lower total carbohydrates than coated almonds. Three main fatty acids detected in all almond products were palmitic (63.2 g kg-1), oleic (727.0 g kg-1) and linoleic (208.0 g kg-1) acids. The overall acceptance means in Roasted almonds, Roasted almonds coated with prickle pear syrup and Roasted almonds coated with algarrobo pod syrup were 6.83, 6.65 and 6.70 in a 9 points hedonic scale, respectively. The peroxide and anisidine values increased in all products. The increase was higher in roasted almonds without coating. CONCLUSION: These results indicated that the syrup coatings provided protection against lipid oxidation in almond products. Prickly pear syrup showed better protection against lipid oxidation.